Sebaran Timbal pada Tanah di Areal Persawahan Kabupaten Sidoarjo - Fitrianah, Listin; Agus Rachmad Purnama (Journal of Research and Technology, 2019)
The existence of this industry in Sidoarjo has the negative potential impact to the environment, namely the accumulation of heavy metals in paddy fields. The magnitude of the impact that can be caused by the presence of lead heavy metals, research is needed that is expected to provide information related to the concentration and distribution of lead on land in Sidoarjo district. The distribution will later be elaborated by mapping using Geographic Information Systems. The purpose of this research is to identify the potential distribution of lead heavy metals in soil and soil in Sidoarjo paddy fields and the potential impact of lead accumulation on the environment. Samples taken were soil in the paddy fields, with 18 location points. The method used in the identification of lead distribution in paddy fields in Sidoarjo district is survey and laboratory testing, where the pattern of lead content distribution in paddy fields is carried out using spatial analysis with the spline with barrier method Arcgis 10.1. The highest distribution of lead content in paddy fields in Wonoayu District, 0.46 ppm. The highest dominant distribution pattern of lead pollution in paddy fields is Wonoayu and Waru sub-districts.